2013
DOI: 10.1097/mpg.0b013e3182774cae
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies and Autoimmune Disease During Treatment of Children With Chronic Hepatitis C

Abstract: Objectives Auto-antibodies were studied in a well-characterized cohort of children with chronic hepatitis C (CHC) during treatment with PEG-IFN and ribavirin to assess the relationship to treatment and development of autoimmune disease. Methods 114 children (5–17 years), previously screened for the presence of high titer autoantibodies, were randomized to Peg-IFN with or without ribavirin. Anti-nuclear (ANA), anti-liver-kidney-microsomal (LKM), anti-thyroglobulin (TG), anti-thyroid peroxidase (TPO), insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…In contrast to these dynamic changes in serum lipoprotein composition and concentration during DAA therapy, we found that the presence or absence of autoantibody to apoA-1 remained largely stable during sofosbuvir-based antiviral therapy and after virological cure over a short follow-up period. This is similar to experience in children with chronic hepatitis C receiving IFN-based anti-viral therapy where autoantibodies were found to be common at baseline, during and after treatment [31]. The vast majority of our patient cohort had received prior IFN-based antiviral therapy and IFN may induce autoimmune disorders or worsen pre-existing autoimmune disorders [32], so it will be important to establish whether the prevalence of anti-apoA-1 IgG is similar in untreated HCV infection.…”
Section: Discussionsupporting
confidence: 73%
“…In contrast to these dynamic changes in serum lipoprotein composition and concentration during DAA therapy, we found that the presence or absence of autoantibody to apoA-1 remained largely stable during sofosbuvir-based antiviral therapy and after virological cure over a short follow-up period. This is similar to experience in children with chronic hepatitis C receiving IFN-based anti-viral therapy where autoantibodies were found to be common at baseline, during and after treatment [31]. The vast majority of our patient cohort had received prior IFN-based antiviral therapy and IFN may induce autoimmune disorders or worsen pre-existing autoimmune disorders [32], so it will be important to establish whether the prevalence of anti-apoA-1 IgG is similar in untreated HCV infection.…”
Section: Discussionsupporting
confidence: 73%
“…This might implicate that autoimmunity induced by HCV should take place early in the course of infection and persist despite elimination of the virus. Compatibly, Molleston and colleagues reported that Peg-IFN-based treatment did not affect serum auto-antibodies in a paediatric cohort with HCV infection 39. In that study, auto-antibodies neither changed during the treatment nor differed between patients with and without viral clearance.…”
Section: Discussionmentioning
confidence: 91%
“…However, the ligand for TgAb, thyroglobulin (Tg), has antigenicity affected by the iodine content within the protein [18,38], and thus TgAb are present non-specifically in different diseases coexisting with the altered iodine intake [39]. More importantly, TgAb can be also found in patients with chronic disorders not involving thyroid [40] or even in healthy patients without any thyroid disease [41]. Thus, clinical impact of the elevated concentrations of TgAb is unreliable, as they were detected non-specifically to thyroid diseases or breast cancer.…”
Section: Discussionmentioning
confidence: 99%